PERLINDUNGAN HUKUM TERHADAP DATA KESEHATAN MELALUI PENGESAHAN RANCANGAN UNDANG-UNDANG PERLINDUNGAN DATA PRIBADI - Endison Ravlindo; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2021)
The development of an increasingly sophisticated era, now personal data has become a commodity that has a high economic value that must receive proper and optimal protection in the practices that exist in society. Some of the regulations regarding the protection of personal data in Indonesia have regulated this, but have not been able to face the challenges that arise regarding the problems that occur. Where this makes the creation of legal certainty as one of the objectives of the law itself. There have been a number of cases that have occurred in recent years, namely the alleged leakage of public personal data that was hacked by third parties irresponsibly for unilateral gain. In this case, because there is no specific and comprehensive regulation that accommodates the protection of personal data itself. In this study, it is intended to examine how legal protection is according to current positive law and according to the Personal Data Protection Bill.